ANTIBACTERIAL ACTIVITY OF SEVERAL PLANTS AND COMBINATION OF SELECTED PLANT WITH SEVERAL ANTIBIOTICS - Yuniarni, Umi
Plants contain various secondary metabolites as antiinfection and have been used as the basis for developing new antibiotic compounds. The study of the traditional medicine efficacy in overcoming infection is needed to to prove the correctness of empirical use scientifically and as a basis for developing new antibiotics. Apart from being antiinfectious, traditional medicines generally have more than one type of pharmacological effect used to prevention, treatment of disease and restoration of health. The use of medicinal plants as traditional medicine together with antibiotics is common in community. This phenomenon can lead to interaction that can affect the antibiotics effectiveness. Therefore, it is necessary to study the interaction of traditional medicine and antibiotics to determine their effectiveness and safety in overcoming the infection. Indonesia is a country with rich biodiversity of plants. Various medicinal plants from Syzygium and other genera have been used in Indonesia to treat infectious diseases such as those affecting respiration, eyes and gastrointestinal tracts. However, scientific reports regarding the potential for antimicrobials derived from Indonesia are still relatively limited. The chemical compounds and mechanism of action of compounds that play a role in antibacterial activity have not been widely reported. This study purposes to evaluate the potential antibacterial activity of several plants in Indonesia against Gram positive bacteria, namely Staphylococcus aureus and Bacillus subtilis as well as Gram negative Pseudomonas aeruginosa and Escherichia coli. This study also aims to assess the effectiveness of the combination of selected plant extracts with several antibiotics and evaluate their mechanism of action in inhibiting bacterial growth. In addition, this study aims to examine the antibacterial activity of the fractions and subfractions of selected plants as well as to examine the chemical compounds and the mechanism of action of the active subfractions that have antibacterial activity. In this study, the extraction of 12 crude drugs from 10 plants using the maceration method with 96% ethanol as a solvent. The crude drugs are Syzygium polycephalum leaves, Syzygium polyanthum leaves, Syzygium malaccense leaves, Syzygium samarangense leaves, Syzygium myrtifolium leaves, Psidium cattleianum leaves, Graptophyllum pictum leaves, leaves and rind of Nephelium lappaceum, two varieties of Plectranthus scutellarioides leaves (jawer kotok) and leaves of Kleinhovia hospita. Antibacterial activity test was carried out using the agar diffusion method with a perforator. The selected plant extracts with the best antibacterial activity were determined based on the largest inhibition at the same concentration and the activity spectrum in inhibiting all tested bacteria. The selected plants were extracted using two methods, namely reflux and maceration to determine the optimum extraction method in attracting compounds that have antibacterial activity. The mechanism of the extract in inhibiting bacterial growth was evaluated using the Scanning Electron Microscopy (SEM) method. The effect of a combination of selected plant extracts and antibiotics was carried out using a time kill curve assay. Meanwhile, to determine the active compounds that play a role in antibacterial activity, the compound component were separated. This process begins with graded maceration, fractionation and subfractionation. The selected plants were extracted by maceration using increasing polarity solvent to separate the compounds based on polarity. The active compound in the extract was monitored by thin-layer chromatography (TLC)-bioautography. The selected extract was then fractionated by vacuum liquid chromatography, and the selected fraction was sub-fractionated by classical column chromatography. The compounds in the active subfraction were monitored using TLC and high-performance liquid chromatography. The mechanism of action of the compounds in the subfraction was carried out by in silico against Penicillin Binding Protein. The screening results for antibacterial activity against twelve plants extracts showed that jambu bol (Syzygium malaccense) and rambutan (Nephelium lappaceum) leaves extracts had antibacterial potential compared to the other test extracts. However, based on the ability to inhibit P. aeruginosa, jambu bol leaves extract showed better activity than rambutan leaves. Thus, jambu bol leaves were chosen as the extract used in further research. The jambu bol leaves extract which was obtained by the maceration method (hereinafter referred to as direct-ethanol extract) showed better activity than that from the reflux method, so for further testing, the jambu bol leaves were extracted by maceration. Analysis of the mechanism of jambu bol leaves extract using the SEM method showed that the extract caused S. aureus and P. aeruginosa cells to lysis. The combination of extracts with the antibiotic amoxicillin, ciprofloxacin, and tetracycline showed synergistic characteristic. The antibacterial activity test using the agar diffusion method showed the nhexane extract did not show activity, while the ethyl acetate and ethanol extracts showed inhibition against all tested bacteria. Based on the consideration of the separation process in the fractionation and sub-fractionation, ethyl acetate extract was chosen for further tests. The results of TLC bioautography showed that ethyl acetate extract could inhibit the growth of Gram-positive bacteria and had no activity against those of Gramnegative. Further study was thus focused on ethyl acetate extract against Grampositive bacteria, namely S. aureus and B. subtilis. The fractionation of ethyl acetate extract showed that the F2 fraction provided the best antibacterial activity among other fractions. Furthermore, sub-fractionation was carried out on the F2 fraction. The antibacterial activity test against subfraction showed that SF3 and SF4 subfraction provided better antibacterial activity than other subfractions. Monitoring of subfraction compounds with HPLC showed that SF3 contained rutin and myricetin, while SF4 contained rutin, myricetin, quercetin, and kaempferol. In silico testing indicated that SF4, rutin, myricetin, kaempferol, and quercetin showed stability and affinity for penicillin-binding protein (PBP) in S. aureus. The study results provide scientific data on the use of jambu bol leaves in the treatment of infectious diseases. The study of interaction of jambu bol with several antibiotics indicate synergistic characteric leading to reduced time to inhibit bacterial growth. Jambu bol leaves contained rutin, myricetin, kaempferol and quercetin which are thought to play a role in antibacterial activity. .